MARKETING STRATEGY FOR WATER SPINACH IN SANGGAOEN VILLAGE, LOBALAIN SUB-DISTRICT, ROTE NDAO REGENCY - Sooai, Junaldi; Bano, Maria; Elvani, Siska (Undana Press, 2025)
Research on Marketing Strategies for Water Spinach Commodities in Sanggaoen Village, Lobalain District, Rote Ndao Regency aims to (1) identify internal and external factors in the marketing of water spinach commodities in Sanggaoen Village and (2) determine the marketing strategies for water spinach commodities in Sanggaoen Village. This research was conducted in September 2024 in Sanggaoen Village, Lobalain District, Rote Ndao Regency. The sources in this research consist of 45 water spinach farmers. The method used in data collection is the interview method guided by a questionnaire. To determine the marketing strategy, a SWOT analysis was used. The research results show that the factors determining the marketing of water spinach commodities include internal factors consisting of strengths such as a strategic farming location, having regular customers, owning transportation, and the entrepreneur selling directly, and weaknesses such as the product's short shelf life, inability to independently set the price of water spinach, and insufficient use of technology for promotion. External factors that influence include opportunities such as the presence of many restaurants, the use of social media for marketing, and a wide market share opportunity. Threats include fluctuations in water spinach prices, similar agricultural businesses, and diseases affecting water spinach. The marketing strategies implemented by farmers in Sanggaoen Village are (1) utilizing a network of regular customers, (2) providing incentives to regular customers, (3) conducting training for farmers to use digital technology, and (4) implementing a pre-order system.SWOT